2023
DOI: 10.1093/treephys/tpad022
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional reprogramming during recovery from drought stress in Eucalyptus grandis

Abstract: The importance of drought as a constraint to agriculture and forestry is increasing with climate change. Genetic improvement of plants’ resilience is one of the mitigation strategies to curb this threat. Although recovery from drought stress is important to long term drought adaptation and has been considered as an indicator of dehydration tolerance in annual crops, this has not been well-explored in forest trees. Thus, we aimed to investigate the physiological and transcriptional changes during drought stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…under abiotic stress). Recently, RNAseq analysis of the E. grandis stem transcriptome has revealed that genes associated with growth and metabolism were downregulated during drought, while responses to reactive oxygen species (ROS) and phytohormone signaling pathways were upregulated ( Teshome et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…under abiotic stress). Recently, RNAseq analysis of the E. grandis stem transcriptome has revealed that genes associated with growth and metabolism were downregulated during drought, while responses to reactive oxygen species (ROS) and phytohormone signaling pathways were upregulated ( Teshome et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…To uncover potential homologs of AQP genes associated with responses to drought stress, we conducted an analysis of the RNAseq dataset for Eucalyptus grandis exposed to drought stress (DS) and subsequent rewatering (RW) conditions as described in Teshome et al . (2023).…”
Section: Resultsmentioning
confidence: 99%
“…To uncover potential homologs of AQP genes associated with responses to drought stress, we conducted an analysis of the RNAseq dataset for Eucalyptus grandis exposed to drought stress (DS) and subsequent rewatering (RW) conditions as described in Teshome et al (2023). We employed a significance threshold with an adjusted p-value of less than 0.05 and a log fold change (logFC) greater than 2 to identify differentially expressed genes (DEGs).…”
Section: Expression Profile Of Egaqps Under Drought Stress and Rewate...mentioning
confidence: 99%